Crystal structure, Hirshfeld analysis and molecular docking with the vascular endothelial growth factor receptor-2 of (3Z)-5-fluoro-3-(hydroxyimino)indolin-2-one Martins Bianca Barreto - Martins, Bianca Barreto; Bresolin, Leandro; De Farias, Renan Lira [UNESP]; De Oliveira, Adriano Bof; Gervini, Vanessa Carratu (International Union of Crystallography (IUCr), 2017)
The reaction between 5-fluoroisatin and hydroxylamine hydrochloride in acidic ethanol yields the title compound, C8H5FN2O2, whose molecular structure matches the asymmetric unit and is nearly planar with an r.m.s. deviation for the mean plane through all non-H atoms of 0.0363 Å. In the crystal, the molecules are linked by N-H·N, N-H·O and O-H·O hydrogen-bonding interactions into a two-dimensional network along the (100) plane, forming rings with R2 2 (8) and R1 2 (5) graph-set motifs. The crystal packing also features weak π-π interactions along the [100] direction [centroid-To-centroid distance 3.9860 (5) Å]. Additionally, the Hirshfeld surface analysis indicates that the major contributions for the crystal structure are the O·H (28.50%) and H·F (16.40%) interactions. An in silico evaluation of the title compound with the vascular endothelial growth factor receptor-2 (VEGFR-2) was carried out. The title compound and the selected biological target VEGFR-2 show the N-H·O(GLU94), (CYS96)N-H·O(isatine) and (PHE95)N-H·O(isatine) intermolecular interactions, which suggests a solid theoretical structure-Activity relationship.
Keywords: crystal structure; Hirshfeld surface analysis; isatin derivative-VEGFR-2 in silico evaluation